Nuclear battery using foamed aluminum as ohmic contact electrode material

By using foam aluminum as the ohmic contact electrode material in a β-radiation volt effect nuclear battery and forming a PIN junction on the GaAs substrate, the problem of environmental conditions and metal materials having less impact on output power in the prior art is solved, and higher output power and energy conversion efficiency is achieved.

CN119724667APending Publication Date: 2025-03-28ELECTRIC POWER RES INST OF GUANGXI POWER GRID CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411619890.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing β-radiation volt-effect nuclear batteries have little research on the impact of environmental conditions and metal materials on output power, resulting in the need to improve energy conversion efficiency and material utilization.

Method used

Aluminum foam is used as the ohmic contact electrode material, and a PIN junction is formed on the GaAs substrate through low-voltage chemical vapor deposition technology, and a 260nm foam aluminum electrode is sputtered on both sides of the electrode to increase the probability of decaying particles entering the transducer device.

Benefits of technology

The output power and energy conversion efficiency of β-radiation volt-effect nuclear batteries are improved, the decay energy of the radiation source is maximized, and gallium arsenide is selected as the semiconductor material by matching the electron affinity potential and metal escape work of the semiconductor material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724667A_ABST
    Figure CN119724667A_ABST
Patent Text Reader

Abstract

The invention discloses a nuclear battery taking foam metal as an ohmic contact electrode material, which is characterized in that the foam metal is selected to replace previously used metal as an electrode material, and a proper semiconductor material is selected as a material of a transducer by matching the work function of the metal with the electron affinity of a semiconductor. A radioactive source is taken in from the P layer, electron hole pairs are generated through the radiation ionization effect, current is formed under the action of a built-in electric field, and conversion from decay energy of the radioactive isotope source to electric energy is achieved; the negative influence of the beta-radiation-volt-effect nuclear battery caused by the fact that the metal conductive material provides an ohmic contact electrode for the beta-radiation-volt-effect nuclear battery and a power grid needed for transmitting current to the outside is reduced, and the conversion efficiency of the beta-radiation-volt-effect nuclear battery is improved. Therefore, the number of decay particles of the radioactive isotope source of the nuclear battery entering the transducer is increased, the decay energy entering the transducer is improved, and the output performance of the nuclear battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nuclear energy technology application, and specifically relates to a nuclear battery using foamed aluminum as an ohmic contact electrode material. Background Art

[0002] With the rapid development of micro-electromechanical system (MEMS) technology, nuclear batteries have become an ideal choice for MEMS power sources due to their miniaturization, integration, high energy density, long service life and independence from external energy (fossil fuels and solar energy). There are three main types of micro-nuclear batteries: micro-thermoelectric conversion nuclear batteries, beta-radiation voltaic effect nuclear batteries and radiation photovoltaic effect nuclear batteries. Among them, beta-radiation voltaic effect nuclear batteries have attracted widespread attention because they are basically the same as solar cells in basic structure and energy conversion devices, and only differ in energy sources. Beta-radiation voltaic effect nuclear batteries are mainly composed of two parts: a radiation source and a transducer device. After the isotope radioactive source decays to produce beta particles, the built-in electric field of the transducer device is used to separate the radiation-generated electron-hole pairs, and then the electrodes on both sides collect electrons and holes to form radiation-generated currents to complete the conversion of decay energy into electrical energy. At present, the research on beta-radiation voltaic effect nuclear batteries is mainly focused on continuously optimizing the structure of the transducer device, finding semiconductor materials with wider bandgap, and the matching degree between the radiation source and the semiconductor material. In the selection of radiation sources, for the sake of protection, avoiding damage to surrounding electronic equipment and service life, pure beta radiation sources with higher specific power are generally selected as the radiation sources of beta radiation voltaic effect nuclear batteries. Research has found that in the selection of semiconductor materials, semiconductor materials with large bandgap width and small intrinsic carrier concentration are suitable for the preparation of semiconductor transducer devices with low reverse saturation current, which will help to improve the open circuit voltage, electrical output performance, energy conversion efficiency and radiation resistance of nuclear batteries. At present, the semiconductor materials used in transducer devices have developed from the first generation of single crystal materials to the third generation of wide bandgap semiconductor materials, such as SiC and GaN.

[0003] In the beta radiation voltaic effect nuclear battery, the radiation source has evolved from the initial radiation source 147Pm to the radiation source 3H, the radiation source 63 Ni, radioactive source 90 Sr / 90Y, etc.; in the selection of semiconductor materials, it has developed from single crystal silicon with low cost, simple and mature process, perfect doping concentration technology and excellent quality to polycrystalline silicon, amorphous silicon, gallium arsenide, gallium nitride, silicon carbide, zinc oxide, diamond, etc.; the types of transducer devices have developed from the initially mature pn junction and pin junction to Schottky diodes. Although the materials of transducer devices are currently developing in the direction of wide bandgap, in the simulation calculation and production of β-radiation voltaic effect nuclear batteries, it is also necessary to consider the matching degree between the maximum decay energy of the radiation source and the energy damage threshold of the semiconductor material to achieve the greatest possible energy conversion efficiency and improve the utilization rate of the materials. At present, the research on β-radiation voltaic effect nuclear batteries mainly focuses on changing the structure of transducer devices to improve the output power and energy conversion efficiency of β-radiation voltaic effect nuclear batteries, but there are few related studies on the influence of environmental conditions and metal materials on the output power of β-radiation voltaic effect nuclear batteries. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a nuclear battery using foamed aluminum as an ohmic contact electrode material.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a nuclear battery using foamed aluminum as an ohmic contact electrode material, characterized in that: the nuclear battery using foamed aluminum as an ohmic contact electrode material comprises, from top to bottom, the following layers in sequence:

[0008] Radioactive Sources 90 Sr / 90 Y layer (100);

[0009] P-side electrode (200);

[0010] An active layer (300);

[0011] a lower waveguide layer (400);

[0012] A buffer layer (500);

[0013] and an N-side electrode (600).

[0014] As a preferred embodiment of the preparation method of the present invention, the nuclear battery radiation source 90 Sr / 90 The beta particles emitted by the Y layer (100) generate electron-hole pairs through the radiation ionization effect. Under the action of the built-in electric field, the electrons and holes are separated and collected by the P-side electrode (200) and the N-side electrode (600) respectively, forming a current.

[0015] As a preferred solution of the preparation method of the present invention, the P-side electrode (200) and the N-side electrode (600) are foamed aluminum.

[0016] As a preferred embodiment of the preparation method of the present invention, wherein: the thickness of the foamed aluminum is 260 nm.

[0017] As a preferred solution of the preparation method of the present invention, the doping concentration of the active layer (300) is 1.1×10 19 cm -3 , thickness is 50nm.

[0018] As a preferred solution of the preparation method of the present invention, the doping concentration of the lower waveguide layer (400) is 1.2×10 18 cm -3 ~1.4×10 18 cm -3 , with a thickness of 11000nm~12000nm.

[0019] As a preferred embodiment of the preparation method of the present invention, the doping concentration of the buffer layer (500) is 1.8×10 16 cm -3 , thickness is 1000nm.

[0020] As a preferred embodiment of the preparation method of the present invention, the radiation source 90 Sr / 90 The Y layer (100) has a surface emission activity of 200 mci / cm -2 Rectangular solid-state radiation source 90 Sr / 90 Y.

[0021] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a nuclear battery using foamed aluminum as an ohmic contact electrode material.

[0022] As a preferred embodiment of the preparation method of the present invention, the preparation method of a nuclear battery using foamed aluminum as an ohmic contact electrode material is characterized by comprising:

[0023] Take a 1000nm thick N-type GaAs substrate, and use low-pressure chemical vapor deposition technology to grow a low-doped N-type epitaxial layer on the N-type GaAs substrate; diffuse a high-doped P region in the low-doped N-type epitaxial layer to form a PIN junction, and finally take the formed basic PIN junction and sputter 260nm foam aluminum electrodes on both sides of the P-type and N-type semiconductors.

[0024] As a preferred embodiment of the preparation method of the present invention, the doping concentration of the N-type GaAs is 1.8×10 16 cm -3 The N-type epitaxial layer has a thickness of 12000nm and a doping concentration of 1.2×10 18 cm -3 ; The thickness of the highly doped P region is about 50nm, and the doping concentration is 1.1×10 19 cm -3 .

[0025] Beneficial effects of the present invention:

[0026] The present invention provides a beta radiation voltaic effect nuclear battery using foamed aluminum as an ohmic contact electrode material. Compared with a beta radiation voltaic effect nuclear battery using foamed aluminum as an ohmic contact electrode material, the beta radiation voltaic effect nuclear battery using foamed aluminum as an ohmic contact electrode material has more decay particles entering the energy conversion device, that is, the decay energy entering the energy conversion device is higher; at the same time, since foamed aluminum is used as the ohmic contact electrode material, in order to obtain higher output performance and battery conversion efficiency, the metal work function is matched and selected with the semiconductor electron affinity, and gallium arsenide is determined to be selected as the semiconductor material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0028] Figure 1 This is a schematic diagram of the structure of a beta-radiation voltaic effect nuclear battery using foamed aluminum as the ohmic contact electrode material. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0032] Unless otherwise specified, the raw materials used in the examples of the present invention are commercially available.

[0033] Example 1

[0034] This embodiment provides a structure of a nuclear battery using foamed aluminum as an ohmic contact electrode material:

[0035] Combination Figure 1 The present invention is further described in detail. The structure of the nuclear battery in the present invention is as follows from top to bottom:

[0036] Radioactive Sources 90 Sr / 90 Y (100), P-side electrode (200), active layer P-GaAs (300), lower waveguide layer I-GaAs (400), buffer layer N-GaAs (500), N-side electrode (600), load (700), wire 1 (800), wire 2 (900).

[0037] The beta particles emitted by the radiation source generate electron-hole pairs through the radiation ionization effect. Under the action of the built-in electric field, the electrons and holes are separated and collected by the electrodes on both sides respectively, forming a current.

[0038] Example 2

[0039] This embodiment provides a method for preparing a nuclear battery using foamed aluminum as an ohmic contact electrode material:

[0040] Select a 1000nm thick N-type (doping concentration 1.8×10 16 cm -3 )GaAs is used as the substrate. A layer with a thickness of 12000nm is grown on the N-type GaAs substrate using low-pressure chemical vapor deposition technology, and the doping concentration is 1.2×10 18 cm -3 A layer with a doping concentration of 1.1×10 19 cm-3 A highly doped P region with a thickness of about 50nm is formed to form a PIN junction. Finally, taking the basic PIN junction formed, 260nm foam aluminum electrodes are sputtered on both sides of the P-type and N-type semiconductors respectively.

[0041] Example 3

[0042] This embodiment performs theoretical simulation on the output performance of the nuclear battery to obtain optimized parameters of each layer of the battery. The optimization results obtained by the present invention are as follows:

[0043] In the simulation process of the output performance of the β-radiovoltaic effect nuclear battery: first, it is necessary to determine the type of radioactive source and the emission activity of the radioactive source. The particles released by the decay of the radioactive isotope source will undergo self-absorption during the transportation process inside the source. Without considering the self-absorption effect, as the thickness of the radioactive source increases, the particle emission activity increases. However, due to the existence of the self-absorption effect, the energy loss inside the radioactive source also increases with the increase of the thickness of the radioactive source. Therefore, in the selection of the radioactive source, the particle emission activity is generally selected as large as possible through MCNP simulation and the waste of the radioactive source caused by the self-absorption effect is avoided as much as possible; secondly, MCNP and COMSOL are used to simulate the performance of the nuclear battery. Through MCNP simulation of the energy deposition of radioactive sources with different surface emission activities in the transducer device, the generation rate of electron-hole pairs is obtained by calculation, and it is found that the generation rate generally shows an exponential decline trend with the increase of penetration depth. The carrier concentration distribution can be simulated by COMSOL using the fitting curve of the electron-hole pair generation rate simulated by MCNP, and the recombination rate distribution of electron-hole pairs can be obtained by using the Shockley-Read-Hall recombination model, and the battery output performance parameters such as the short-circuit current, open-circuit voltage, and output power of the nuclear battery can be obtained. Then, the output performance obtained under different doping concentrations and thicknesses of semiconductor materials can be compared to obtain the best output performance; finally, the most suitable metal material is selected as the metal electrode for the electron affinity of the semiconductor material selected for the energy conversion device and the work function of the metal. Since the electron affinity of GaAs is 4.17eV and the work function of metal aluminum is 4.2eV, and since foamed aluminum can obtain better β-radiation voltaic effect nuclear battery output performance than metal aluminum, foamed aluminum is selected as the ohmic contact electrode.

[0044] The radiation source has a surface emission activity of 200 mci / cm -2 Rectangular solid-state radiation source 90 Sr / 90 Y.

[0045] The energy conversion device uses GaAs that matches aluminum as a semiconductor material, wherein the energy conversion device uses a pin structure.

[0046] The doping concentration of the P-GaAs layer is 1.1×10 19 cm -3 , with a thickness of 50nm. Heavy doping of this layer is conducive to forming a good ohmic contact with the electrode. In addition, the area with a high rate of electron-hole pair generation in the nuclear battery should be consistent with the depletion layer as much as possible, so the thickness of this layer should be as thin as possible.

[0047] The doping concentration of the I-GaAs layer is 1.2×10 18 cm -3 ~1.4×10 18 cm -3 , with a thickness of 11000nm to 12000nm, mainly separates electron-hole pairs through the built-in electric field of this layer, but due to the radiation source 90 Sr / 90 The activity density of Y is too strong. In order to better utilize the decay energy of the radiation source, the thickness of this layer is determined by calculating the minority carrier diffusion length of GaAs and the width of the depletion layer.

[0048] The doping concentration of the N-GaAs layer is 1.8×10 16 cm -3 , with a thickness of 1000 μm. The existence of this layer is mainly to improve the stability of the transducer device, improve the performance of the device, and increase the life of the device, so it does not need to be too thick.

[0049] The P-side electrode and the N-side electrode are both foamed aluminum, and the thickness is 260nm. By using foamed aluminum instead of metal as the ohmic contact electrode material, the probability of the decay energy of the radioactive source entering the energy conversion device is increased, thereby improving the output power and battery conversion efficiency of the beta radiation voltaic effect nuclear battery. In addition, wires are welded on the electrode surface to facilitate the connection of the external circuit.

[0050] In the research on beta radiation voltaic effect nuclear batteries, generally involved are the self-absorption effect of the radiation source, the energy deposition of the decay energy of the radiation source in the transducer device, and the transmission of carriers in the transducer device and other aspects; the present invention mainly uses foamed aluminum as the ohmic contact electrode material to inject more beta particles into the transducer device, reduce consumption, and thus improve the output performance and energy conversion efficiency of the beta radiation voltaic effect nuclear battery.

[0051] Comparative Example 1

[0052] The difference from Example 1 is that the foamed aluminum is replaced by metal aluminum.

[0053] The beta-radiation voltaic effect nuclear battery uses foamed aluminum as the ohmic contact electrode material. Compared with the beta-radiation voltaic effect nuclear battery using metal as the ohmic contact electrode material, more decay particles enter the energy conversion device, that is, the decay energy entering the energy conversion device will be higher; at the same time, since foamed aluminum is used as the ohmic contact electrode material, in order to obtain higher output performance and battery conversion efficiency, the metal work function and the semiconductor electron affinity are matched and selected, and gallium arsenide is determined to be used as the semiconductor material.

[0054] In summary, the present invention provides a beta radiation voltaic effect nuclear battery using foamed aluminum as the ohmic contact electrode material. Foamed aluminum is mainly used as the ohmic contact electrode material to inject more beta particles into the transducer device, reduce consumption, thereby improving the output performance and energy conversion efficiency of the beta radiation voltaic effect nuclear battery and making greater use of the decay energy of the radioactive source.

[0055] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A nuclear battery using aluminum foam as an ohmic contact electrode material, characterized in that: The nuclear battery using aluminum foam as the ohmic contact electrode material comprises, from top to bottom, the following layers of structure: Radioactive Sources 90 Sr / 90 Y layer (100); P-side electrode (200); An active layer (300); a lower waveguide layer (400); A buffer layer (500); and an N-side electrode (600).

2. The nuclear battery using aluminum foam as the ohmic contact electrode material as claimed in claim 1, characterized in that: Said 90 Sr / 90 The beta particles emitted by the Y source pass through the foam aluminum electrode. By replacing the metal aluminum material with the foam aluminum electrode, more decay energy is deposited in GaAs to form electron-hole pairs, which form current under the action of the built-in electric field.

3. The nuclear battery using foamed aluminum as the ohmic contact electrode material as claimed in claim 1, characterized in that: The P-side electrode (200) and the N-side electrode (600) are foamed aluminum.

4. The nuclear battery using foamed aluminum as the ohmic contact electrode material as claimed in claim 3, characterized in that: The thickness of the foamed aluminum is 260 nm.

5. The nuclear battery using foamed aluminum as the ohmic contact electrode material as claimed in claim 1, characterized in that: The doping concentration of the active layer (300) is 1.1×10 19 cm -3 , thickness is 50nm.

6. The nuclear battery using foamed aluminum as the ohmic contact electrode material as claimed in claim 1, characterized in that: The doping concentration of the lower waveguide layer (400) is 1.2×10 18 cm -3 ~1.4×10 18 cm -3 , with a thickness of 11000nm~12000nm.

7. The nuclear battery using foamed aluminum as the ohmic contact electrode material as claimed in claim 1, characterized in that: The doping concentration of the buffer layer (500) is 1.8×10 16 cm -3 , thickness is 1000nm.

8. The nuclear battery using foamed aluminum as the ohmic contact electrode material as claimed in claim 2, characterized in that: The radiation source 90 Sr / 90 The Y layer (100) has a surface emission activity of 200 mci / cm -2 Rectangular solid-state radiation source 90 Sr / 90 Y.

9. The method for preparing a nuclear battery using foamed aluminum as an ohmic contact electrode material as claimed in claims 1 to 8, characterized in that: include, Take a 1000nm thick N-type GaAs substrate, and use low-pressure chemical vapor deposition technology to grow a low-doped N-type epitaxial layer on the N-type GaAs substrate; diffuse a high-doped P region in the low-doped N-type epitaxial layer to form a PIN junction, and finally take the formed basic PIN junction and sputter 260nm foam aluminum electrodes on both sides of the P-type and N-type semiconductors.

10. The preparation method according to claim 9, characterized in that: The N-type GaAs doping concentration is 1.8×10 16 cm -3 The N-type epitaxial layer has a thickness of 12000nm and a doping concentration of 1.2×10 18 cm -3 ; The thickness of the highly doped P region is about 50nm, and the doping concentration is 1.1×10 19 cm -3 .